Interactions 2 : Grammar - Werner, Patricia K.; Nelson, John P.; Hyzer, Kessia; Mitchell Church, Mary (United States : McGraw-Hill, 2002)
The themes are integrated across proficiency levels and the levels are articulated across skill strands.
1. Educations and student life 2. City' life 3. Business and money 4. Jobs and professions 5. Lifestyles around the world 6. Global connections and other 6 chapters more
Incluye contenido
Keywords: GRAMMAR; GRAMATICA